Indexes of citrulline metabolism in rat liver under the toxic injury against the background of alimentary protein deficiency. - Kopylchuk, H. P.; Nykolaichuk, I. M.; Lylyk, I. S. (Ukr. Biochem. J., 2020)
It is known that citrulline is converted into arginine in the series of metabolic transformations. Results of our previous studies showed that acetaminophen-induced toxic injury on the background of the alimentary deprivation of protein is accompanied by a decrease in arginine level in rat hepatocytes, but citrulline liver metabolism at these conditions remains incompletely clear. In this work, the content of citrulline in the rat liver mitochondrial and cytosolic fractions and the activity of citrulline-degrading enzymes – argininosuccinate synthase and argininosuccinate lyase were investigated. It was found that in the mitochondrial fraction a maximal reduction of the citrulline levels occurred after administration of acetaminophen toxic doses regardless of the protein amount in the ration, while in the cytosolic fraction the alimentary protein deficiency was a key factor in decreasing the activity of argininosuccinate synthase and arginino-succinate lyase. The data obtained indicated the disturbances of the urea cycle functioning and explained the decrease of L-arginine level in hepatocytes in conditions of acetaminophen-induced toxic injury against the background alimentary protein deficiency.
Keywords: L-сitrulline; аrgininosuccinate synthetase; argininosuccinate lyase; acetaminophen; toxic injury; alimentary deprivation of protein